Les instituteurs bilingues dans les mobilisations autochtones du Nayarit (Mexique) - Daniele Inda (Cahiers des Amériques Latines)
The article aims to contribute to the understanding the role of Amerindian teachers in the emergence of indigenous movements. It shows that their propensity for identity activism is based on dispositions acquired through their professional socialization within indigenist institutions. The emergence of these movements is thus a continuation of indigenist policies, rather than a break with them.